Lung Ultrasound in Patients With SARS‐COV‐2 Pneumonia: Correlations With Chest Computed Tomography, Respiratory Impairment, and Inflammatory Cascade. (17th September 2021) - Fratianni, Gerardina; Malfatto, Gabriella; Perger, Elisa; Facchetti, Luca; Pini, Laura; Bosco, Miriam; Cernigliaro, Franco; Perego, Giovanni B.; Facchini, Mario; Badano, Luigi P.; Parati, Gianfranco
Abstract : Objectives: Lung ultrasound (LUS) might be comparable to chest computed tomography (CT) in detecting parenchymal and pleural pathology, and in monitoring interstitial lung disease. We aimed to describe LUS characteristics of patients during the hospitalization for COVID‐19 pneumonia, and to compare the extent of lung involvement at LUS and chest‐CT with inflammatory response and the severity of respiration impairment. Methods: During a 2‐week period, we performed LUS and chest CT in hospitalized patients affected by COVID‐19 pneumonia. Dosages of high sensitivity C‐reactive protein (HS‐CRP), d ‐dimer, and interleukin‐6 (IL‐6) were also obtained. The index of lung function ( P / F ratio) was calculated from the blood gas test. LUS and CT scoring were assessed using previously validated scores. Results: Twenty‐six consecutive patients (3 women) underwent LUS 34 ± 14 days from the early symptoms. Among them, 21 underwent CT on the same day of LUS. A fair association was found between LUS and CT scores ( R = 0.45, P = .049), which became stronger if the B‐lines score on LUS was not considered ( R = 0.57, P = .024). LUS B‐lines score correlated with IL‐6 levels ( R = 0.75, P = .011), and the number of involved lung segments detected by LUS correlated with the P / F ratio ( R = 0.60, P = .019) but not with HS‐CRP and d ‐Dimer levels. No correlations were found between CT scores and inflammations markers or P / F . Conclusion: In patients with COVID‐19 pneumonia, LUS was correlated with both the extent of the inflammatory response and the P / F ratio.